Do Women Have a Less Entrepreneurial Personality? - Ola Bengtsson; Tino Sanandaji; Magnus Johannesson (Research Institute of Industrial Economics (IFN), 2012)
A striking fact about entrepreneurship is that the number of male entrepreneurs greatly exceed the number of female entrepreneurs. We use detailed survey data from Sweden to study to what extent this gender gap can be explained by gender differences in personality. We show that women have markedly different psyche than men (11 out of 14 traits differ), and that entrepreneurs have markedly different psyche than others (8 out of 14 traits differ). However gender differences in traits do not reduce women's likelihood of being an entrepreneur in a one-sided way. We find that, in aggregate, gender differences in personality traits can explain a modest part of the gender gap in entrepreneurship: our estimates suggest 21%32%. We also document that personality traits that distinguish entrepreneurs from others are generally not more prevalent among the non-entrepreneurial self-employed. This finding highlights that entrepreneurship is distinct from other types of self-employment.
Keywords: J16; L26; 330; Entrepreneurship; Self-employment; Gender differences; Personality traits